Introduction to pascal with application in science and engineering. - Finger, Susan; Finger, Ellen (Lexington, Mass. D.C. Health and Co., 1986)
Cover title: Pascal with applications in science and engineering.
Keywords: Engineering; Science; Pascal (Computer program language)